Studi Eksperimental Laju Perpindahan Panas Pada Aktivasi Karbon Bambu Betung Dengan Temperatur Aktivasi 600o C - Sembiring, Juan Axel Maruli; Wijaksana, Hendra; Prananda Surya, I Gede Teddy (Teknik Desain Mekanika, 2021)
Abstract The rapid population growth in almost all countries causes an increasing number of requests for air conditioning systems to get a high level of comfort. The use of a compressor-based air conditioning system or commonly known as AC requires a large amount of electrical energy and can cause global warming. Therefore, an alternative cooling system is needed, one of which is a direct evaporative cooling system. In this system the cooling effect results from the evaporation process that occurs in the pad material that is wetted by water fluid. The evaporative cooling system uses pad material in its application. This study was aimed at finding the effect of variations in carbonization temperature on the characteristics of the heat transfer rate in activated charcoal of bamboo betung whose carbonization temperatures were varied at 400OC (AKBB 400), 500OC (AKBB 500), 600OC (AKBB 600), 700OC (AKBB 700) and 800OC (AKBB 800). This research includes several tests such as SEM test and contact angle test. The final result of this study shows that the AKBB 500 specimen has great potential to be used as a pad material in a direct evaporative cooling system. With the characteristics of the highest heat transfer rate of 3.06 x 10-4 watt. Keywords: Direct Evaporative Cooling, betung bamboo, carbonized, activated, porosity, permeability, fluid mass transfer rate and Heat transfer rate.